Empowering Rural Faith Communities Through Contextual Catechesis - Manfred Habur, Agustinus; Y. Luju, Marselina; Jebarus, Adrianus (Syntax Literate, 2026)
This study investigates the empowering role of contextual catechesis in strengthening rural faith communities, drawing on qualitative research conducted in Stasi Rondo Woing, Sita Parish, Diocese of Ruteng, Indonesia. Data obtained through interviews, observations, and documentation reveal significant challenges, including limited trained catechists, low parishioner participation, insufficient structural support, irregular catechetical practices, and geographic as well as infrastructural constraints. Despite these barriers, the findings highlight substantial opportunities such as strong communal values, openness to faith formation, the presence of committed local leaders, and available pastoral support from parish and diocesan structures. The analysis demonstrates that contextual catechesis—rooted in local culture, adapted to socio-economic realities, and implemented through participatory approaches like Christian Based Communities and family-based catechesis—can enhance engagement, deepen faith understanding, and foster sustainable community formation. The study concludes that contextualized pastoral strategies are essential for empowering rural Catholic communities and ensuring the long-term vitality of their faith life.